Aplikasi Model Pembelajaran Gerlach & Ely dalam Merekontruksi Materi Sejarah Kebudayaan Islam tentang Bani Umayyah di Kelas XI MAN 3 Sleman Yogyakarta - Daimah . (LITERASI (Jurnal Ilmu Pendidikan), 2019)
In SKI learning, especially the material about the Umayyad presented contravational learning material, in which the Muawiyyah as the first caliph of the Banu Umayahh were described as the figure who carried out an Islamic power coup. But in other material, Muawiyyah is described as a wise person. This if it is not addressed appropriately by the teacher and students will potentially occur unexpected perceptions. This study aims to determine the strategy of SKI teachers in reconstructing material about the Umayyads and their impact on students. Data collection is done by interviewing, observing, and documenting and checking the validity of the data by triangulation. The way the teacher reconstructs the Umayyad material is to present learning material from two different points of view. Besides that, the use of the Active Debate method also helped to form positive student understanding. By using the Gerlach and Ely Learning Models researchers offer interactive and interesting learning models that can be implemented in learning the history of Islamic culture.Keywords: Teacher Strategy, SKI, Banu Umayyah, Gerlach and Ely Models